Bakteri Penyebab Infeksi Nosokomial di Ruang Rawat Inap Yang Membahayakan Keselamatan Pekerja Rumah Sakit - Firstika Nabilla Balqis; Susilawati Susilawati (PT. Alahyan Publisher Sukabumi, 2024)
This study identified various bacteria in the hospitalization room that have the potential to cause nosocomial infections, which are a public health problem with a prevalence of between 3.0% to 20.7% and an incidence of 5-10%. This study was conducted through a literature review method, collecting data from various relevant literature sources. This study emphasizes the importance of further research to understand the risk factors and appropriate use of antibiotics in managing nosocomial infections. Suggested preventive measures include changing bed linen daily and conducting routine microbiological examinations to maintain a clean and safe hospital environment. The results showed that the inpatient room is an environment rich in various types of bacteria that can cause nosocomial infections. The bacteria found included Staphylococcus aureus, Bacillus sp., Staphylococcus sp., Enterobacteriaceae, Salmonella sp., Shigella sp., Actinomyces israelii, Vibrio cholerae, Pseudomonas aeruginosa, Klebsiella pneumoniae, Escherichia coli, Proteus sp., Yersinia enterocolitica, Gram-positive coccus, and Micrococcus sp.